Optimising Interference Management in LTE Networks: A Case Study of Bandung City Using Soft Frequency Reuse - Hikmaturokhman, Alfin; Hasanah Putri; Izanoordina Ahmad; Solihah, Normahinta (Buletin Pos dan Telekomunikasi, 2024)
This paper explores the implementation of the Soft Frequency Reuse (SFR) algorithm to optimize interference management in LTE networks. Using Bandung City as a case study, the research evaluates performance metrics such as SINR and throughput across dense urban, urban, and suburban areas. The study employs the Cost-231 propagation model and proportional SINR-based resource allocation to optimize network planning. Results demonstrate that SFR effectively balances resource allocation and interference mitigation under varying traffic conditions, providing practical insights for network operators. These findings validate SFR’s capability to improve LTE network performance across diverse environments.